2013
DOI: 10.1007/s00464-012-2683-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-gripping mesh versus staple fixation in laparoscopic inguinal hernia repair: a prospective comparison

Abstract: The study population was not large enough to obtain statistically significant results. However, the use of SGM for TAPP repairs appeared to give good results in terms of chronic pain, and the incidence of recurrences was not higher than with ST. In our unit, SGM during TAPP repair of inguinal hernias has become the standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
2
21
1
1
Order By: Relevance
“…The low reliability of patch testing with Ti may be attributable to inconsistent validity of patch test reagents, low epidermal penetration of Ti, or the disappearance of Ti hyperreactivity after removal of the causative agent . We recommend that, in patients with a positive history of previous intolerance to Ti products, alternative surgical procedures should be considered, for example, the use of self‐gripping meshes …”
Section: Discussionmentioning
confidence: 99%
“…The low reliability of patch testing with Ti may be attributable to inconsistent validity of patch test reagents, low epidermal penetration of Ti, or the disappearance of Ti hyperreactivity after removal of the causative agent . We recommend that, in patients with a positive history of previous intolerance to Ti products, alternative surgical procedures should be considered, for example, the use of self‐gripping meshes …”
Section: Discussionmentioning
confidence: 99%
“…77,[81][82][83] Self-adhesive meshes specially designed for laparoscopic use are appearing on the market and have shown promising results in terms of reducing pain without changing recurrence patterns. 84,85 …”
Section: Is Mesh Fixation Necessary?mentioning
confidence: 98%
“…Similar to our study results, other studies comparing inguinal hernia repair without fixation to repairs with tacks demonstrated no differences in recurrence or pain. 17 Tack fixation is often purported to reduce the likelihood of hernia recurrence by preventing mesh migration. However, in a meta-analysis, 18 there was no difference in hernia recurrence rates or postoperative pain when comparing laparoscopic inguinal hernia repair with and without the adjunctive use of tacks.…”
Section: Discussionmentioning
confidence: 99%